Motorcycle helmet visor–related facial injury and its potential mechanism of injury: Evidence-based case study. (18th March 2019) - Ramli, Roszalina; Oxley, Jennifer A.
Abstract: Objectives: We encountered an unusual facial laceration wound in relation to motorcycle helmet visor use during our clinical practice. We aimed to assess the prevalence of this unusual facial injury among motorcyclists who sustained facial injuries in selected hospitals and to determine the possible mechanism involved. Methods: We used our prospective cross-sectional substudy involving injured motorcyclists presenting at major trauma hospitals in Southern Klang Valley, Malaysia, between March 2010 and March 2011. of 391 subjects with facial injuries, 2 male motorcyclists sustained this laceration. The wounds were assessed and we believed that each was associated with the helmet visor. One of the visors was collected and the edge was inspected using scanning electron microscopy (SEM). Results: The prevalence of this unusual injury was 0.51% (95% confidence interval, 0.002–0.012) among motorcyclists who sustained facial injuries. Both cases were involved in a head-on collision with their colliding partners and their helmets were intact throughout the crash. The visor in case 1 was intact, but the visor in case 2 was broken. SEM analysis showed that the visor in case 1 had a potential cutting surface. We postulated that with helmet rotation in the forward and downward position and with some degree of visor bending or with a dislodged visor, the sharp-edged visor could potentially severely lacerate the face. Conclusion: This injury affects facial aesthetics and early referral to the facial surgery team is advocated. Documentation of the mechanism of injury, the patient's helmet and visor is obligatory, so that this information can be delivered to the regional road safety authority for preventive measures.